Atherogenic index of plasma is an effective index for estimating abdominal obesity - Shi-Wei Shen; Yun Lu; Feng Li; Cheng-Jian Yang; Yin-Bo Feng; Hong-Wei Li; Wei-Feng Yao; Zhen-Hai Shen (Lipids in Health and Disease, 2018)
Abstract Background The correlation between the atherogenic index of plasma (AIP) and waist circumference (WC) remains unknown. Methods A total of 5351 middle-aged men living in Southeastern China were surveyed using the random stratified cluster sampling method. A WC of 90 cm or greater was indicative of abdominal obesity, and AIP was calculated as follows: log [triglyceride (TG)/high-density lipoprotein-cholesterol (HDL-C)]. Results (1) A significantly higher AIP was observed in subjects with abdominal obesity than in those without abdominal obesity (P < 0·001). (2) Multivariate logistic regression analysis revealed an odds ratio of 1·93, 2·59 and 2·76 for abnormal AIP levels for the second, third and fourth WC quartiles, respectively (all P < 0·001) compared to the first WC quartile as a reference. (3) There was a linear correlation between WC and AIP, and a 1·0 cm increase in WC resulted in a 0·0175 rise in AIP. For AIP corresponding to moderate risk (0·12–0·21), WC was 85–90 cm; for AIP corresponding to high risk (> 0·21), WC was >90 cm. Conclusions AIP of 0·12–0·21 or >0·21 indicates a likelihood of borderline abdominal obesity or abdominal obesity, respectively, and the combination of WC and AIP may increase the specificity and sensitivity for detection of abdominal obesity in clinical practice. The results suggest that AIP may be used as a reference to estimate abdominal obesity.